A taste of health the connection between eating and health - Willumsen, Gail (The Infinite voyage series., 1991)
Shows how diet has direct effect on health. A look at scientific gathering preliminary evidences of a genetic link between health and diet. Cross cultural studies and cholesterol research are addressed.